Resources for learning - Campbell, Suzanne; Raggatt, Peter C. M ([S.l.] : Open University Educational Enterprises, 1982)
The programme illustrates a particular model of curriculum innovation: to the importance of decisions about innovations being made at the school level and to demonstrate that innovations are adapted/not adapted.
Keywords: Comprehensive high schools -- England -- Curricula